2022
DOI: 10.14245/ns.2244152.076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Efficacy of Transforaminal Endoscopy and Microtubular Technology for the Treatment of Lumbar Dumbbell-Shaped Tumors

Abstract: Objective: To analyze differences in feasibility and efficacy between the paravertebral approach and microtubular tumorectomy (PAMT) or percutaneous transforaminal endoscopic tumorectomy (PTET) for the treatment of lumbar dumbbell-shaped tumors.Methods: Clinical data of dumbbell-shaped lumbar tumors in patients treated with PAMT or PTET in our hospital between June 2015 and November 2020 were retrospectively analyzed. The gross total resection (GTR) rate, operation time, estimated blood loss, postoperative hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For tumors located at the thoracic paravertebral or intrathoracic region, some surgeons utilize the L-shaped incision, C-shaped incision, or paraspinal approach to obtain vision while removing these tumors [ 7 , 14 ].Although C- and L-shaped incisions have shorter lengths, amputated thoracic paraspinal muscles cause greater iatrogenic trauma, and the nonstraight incision has poor aesthetics and may hinder wound healing [ 15 ]. In addition, some surgeons have utilized the paraspinal approach to remove tumors [ 16 , 17 ]. The approach has been used more frequently in lumbar spine surgery to reduce the risk of surgical injury.…”
Section: Discussionmentioning
confidence: 99%
“…For tumors located at the thoracic paravertebral or intrathoracic region, some surgeons utilize the L-shaped incision, C-shaped incision, or paraspinal approach to obtain vision while removing these tumors [ 7 , 14 ].Although C- and L-shaped incisions have shorter lengths, amputated thoracic paraspinal muscles cause greater iatrogenic trauma, and the nonstraight incision has poor aesthetics and may hinder wound healing [ 15 ]. In addition, some surgeons have utilized the paraspinal approach to remove tumors [ 16 , 17 ]. The approach has been used more frequently in lumbar spine surgery to reduce the risk of surgical injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience in reducing cerebrospinal fluid leakage after surgery was as follows ( 1 ): 6-0 nylon thread was used to suture the dura intermittently in the dural incision, and the incision was reinforced with epidural bioprotein glue and a meningeal patch ( 2 ); using the muscle splitting technique to separate the paravertebral muscles to reduce muscle damage, which helps to reset the muscles after exiting the tubule, and to close the surgical space and surgical path ( 3 ); The muscle fascia and skin are tightly sutured ( 4 ); The drainage tube does not go through the tubular path, and it was removed as early as possible within 2 days. 5 cases (10.9%) in this group were found to have cavity effusion in the operation area by MRI re-examination, considering the large tumor volume and slow muscle retraction after resection, the effusion caused by the residual cavity disappeared after 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The Eden classification method is currently one of the most common methods for the clinical classification of spinal dumbbell-shaped tumors. Based on the combination of MRI and CT findings, the EDEN classification is more accurate in identifying the type of thoracolumbar dumbbell tumors and helps surgeons to select a better surgical approach ( 1 , 2 ). Most patients with lumbar dumbbell-shaped tumors had a history of low back pain or leg pain, and improvement of symptoms after surgery is one of the main objectives of patients and surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Recent studies have even reported successful endoscopic surgical outcomes for tumor lesions, comparable to traditional surgery. 7 One of the most significant achievements of endoscopic surgery is its ability to largely replace fusion procedures in the treatment of intervertebral foraminal stenosis.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%
“…A positive value indicates disc wedging towards the side of the lesion, while a negative value indicates disc wedging on the side opposite the lesion. In case of L5/S1 level, angle between the upper endplate of L5 and the line connecting the top of bilateral sacral ala, 11 (7) Dynamic SLA: differwww.e-neurospine.org 901 ence of SLA between flexion and extension posture.…”
Section: Radiologic Assessmentmentioning
confidence: 99%